Masked phenomenon: renal and cardiovascular complications; review and updates - Elmukhtar Habas (14777677) (2024)
Background In the in-clinic blood pressure (BP) recording setting, a sizable number of individuals with normal BP and approximately 30% of patients with chronic renal disease (CKD) exhibit elevated outpatient BP records. These individuals are known as masked hypertension (MHTN), and when they are on antihypertensive medications, but their BP is not controlled, they are called masked uncontrolled hypertension (MUHTN). The masked phenomenon (MP) (MHTN and MUHTN) increases susceptibility to end-organ damage (a two-fold greater risk for cardiovascular events and kidney dysfunction). The potential extension of the observed benefits of MP therapy, including a reduction in end-organ damage, remains questionable. Aim and methods This review aims to study the diagnostic methodology, epidemiology, pathophysiology, and significance of MP management in end-organs, especially the kidneys, cardiovascular system, and outcomes. To achieve the purposes of this non-systematic comprehensive review, PubMed, Google, and Google Scholar were searched using keywords, texts, and phrases such as masked phenomenon, CKD and HTN, HTN types, HTN definition, CKD progression, masked HTN, MHTN, masked uncontrolled HTN, CKD onset, and cardiovascular system and MHTN. We restricted the search process to the last ten years to search for the latest updates. Conclusion MHTN is a variant of HTN that can be missed if medical professionals are unaware of it. Early detection by ambulatory or home BP recording in susceptible individuals reduces end-organ damage and progresses to sustained HTN. Adherence to the available recommendations when dealing with masked phenomena is justifiable; however, further studies and recommendation updates are required. Plain language summary Blood pressure tells us how much force the heart exerts on the blood vessels as it pumps blood. Normal blood pressure should be 120/80 mmHg, which generally decreases when a person is sleeping or sitting. High blood pressure or hypertension occurs when the blood pressure is too high. Hidden or masked hypertension (MH) is a type of high blood pressure. Masked hypertension was described as having high blood pressure readings even though the doctor’s office or in-clinic showed normal blood pressure readings. This review aimed to teach people about various kinds of high blood pressure, focusing on hidden (masked) hypertension and how to recognise it, as well as its consequences, treatment, and new information. Other Information Published in: Blood Pressure License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/08037051.2024.2383234